Highly Active Relapsing-Remitting Multiple Sclerosis with Neurofibromatosis Type 1: Radiological Aspects and Therapeutic Challenges – Case Report - Marios Lemonaris; Kleopas A. Kleopa (Case Reports in Neurology, 2024)
Introduction: Multiple sclerosis (MS) is an autoimmune neurodegenerative disease which can rarely co-exist with neurofibromatosis 1 (NF1), a neurocutaneous inherited disorder that predisposes to oncogenesis. Patients who suffer from both conditions can be challenging cases for clinicians, as clinical symptoms and radiological findings may overlap, while MS immune-modifying treatments could further increase the risk of oncogenesis. Case Presentation: In this study, we describe the case of a 27-year-old woman who presented with signs and symptoms of optic neuritis and was then diagnosed with both MS and NF1. As the patient continued to experience MS relapses despite initial interferon-beta treatment, she was subsequently switched to natalizumab and responded well. Conclusion: This case illustrates how MRI lesion differentiation with the co-existence of MS and NF1 can be difficult due to overlaps in lesion characteristics, while treatment decisions can be challenging mainly due to scarce data on the oncogenic risk of MS immunomodulary therapies. Therefore, clinicians need to balance out the risk of malignancy development with the risk of progressive neurological disability when treating such patients.